A SYSTEMATIC AND PRACTICAL METHOD OF LIQUID CHROMATOGRAPHY FOR THE DETERMINATION OF SR AND ND ISOTOPIC RATIOS AND REE CONCENTRATIONS IN GEOLOGICAL SAMPLES - Choon-ki N.; Nakano T.; Tazawa K.; Sakagawa M.; Ito T. (My University, 1995)
A systematic and practical method for the determination of the concentration of the isotopic composition of Sr and Nd and rare-earth elements (REE) from a single sample solution has been developed by combining and improving classical cation-exchange chromatography (CCEC) and modern high-performance liquid chromatography (HPLC). The first step was used to separate Sr and the REE group from a dissolved rock solution by CCEC with a column of large volume and a combination of HCl-HNO3 as an eluent. The second step was used to separate individual REE components present within the REE group by HPLC, simultaneously quantify them with a post-column reaction detector, and collect Nd with a programmable fraction collector. Separated Sr and Nd fractions were then purified by another CCEC with a column of small volume and HCl as an eluent prior to the mass spectrometric analysis. The analytical results obtained for a series of standard rocks showed a good agreement with recommended values to within +/-10% for REE quantification at the 95% confidence level and +/-0.004% (1σ) for the87Sr86Sr and 143Nd144Nd isotopic ratios.